Exploitation of indigenous bacterial antagonists against root-knot nematode, meloidogyne incognita (kofoid and white ) chitwood - Vishnu J S (Department of Nematology, College off Agriculture, 2018)
An investigation entitled "Exploitation of indigenouos bacterial antagonists against root-knot nematode, Meloidogyne incognita (Kofoid and White)Chitwood" was carried out at department of nematology, college of agriculture, vellayani during 2016-2018. The objective was to isolate indigenous bacterial antagonists and to evaluate their bio control potential against root-knot nematode. A survey was conducted in three agro ecological units viz., high ranges in Idukki, midlands in Thrissur and low lands in Thiruvananthapuram districts during 2016-17 for isolation of indigenous bacteria. A total of sixty two soil and fifty eight root samples were collected from the rhizosphere of cardamon, pepper,rice and vegetables by randon sampling. Thirty eight bacterial colonies showing characteristics similar to Bacillus and Pseudomonas were selected and brought into pure culture by streak plate technique. Twelve isolates which showed 66.00 to 94.00 percent mortality of M. icognita juiveniles were selected after preliminary screening under in vitro condidtions. Morphological and cultural characteristics and colony forming units of twelve isolates were studied.. Bio efficacy study of twelve isolates on M. incognita juveniles revealed that four isaolates at lowest concentration (25%) showed 58.00 to 72.50 percent mortality of M. incognita juveniles 72 hr after exposure. Isolate 1,2,3 and 4 showed 91.00, 94.00,87.00 and 81.50 percent mortality of M. incognira juveniles at 100 percent concentration, 72 hr after treatment respectively. Cell free extracts of these four isolates were screened for ovicidal and larvicidal effects against M. incognita under in vitro. Sterile water and plain broth were maintained as control. Results of the in vitro screening studies revealed dthat cell free extract of isolate 1 amd 2 (100% concentration ) were effective in inhibiting the egg hatching at three to eight days after treatment (0.20 to 7.96 percent). These two isolates at (100% concentration ) also showed statistically significant superiority over all other isolates allowing only 4.65 to 7.96 per cent egg hatching compared to control on 6th, 7th and 8th day after treatment. Isolate 2 at 100% concentration was effective in increasing the mortality of M. incognita juveniles at 24, 48 and 72 hr after treatment (27.00 to 94.00 percent). Isolate 1 and Isoslate 2 (100% concentration) were found to be statistically on par in exhibiting 51.50 and 54.00 per cent juvenile mortality respectively after 48 hr of treatment. Based on larvicidal and ovicidal properties of cell free extracts, two isolates were selected for pot culture experiment to find out the efficacy in comparison with NBAIR isolate (Bacillus subtilis), organic amendment (neem cake) and chemical cartap hydrochloride). The results revealed that soil drenching with isolate 2 (1*10 7 cfu mL-1)@ 50 mL pot-1 was effective in reducing the nemotode population in soil (72.69 per cent) and root(82.33 per cent ) and it was significantly superior to B.subtilis, Isolate 1 and neem cake. Efficacy of Isolate 2 was found to be statistically on par with chemical, cartap hydrochloride in reducing the number of galls (73.92 to 75.64 percent and females (60.00 to 68.57 per cent ) in root. Isolate 2 was significantly superior to all other treatments in improving the growth parameters (fresh plant weight and root weight). Significantly superior yield was also recordede by isolate 1 and 2 in comparison with neem cake and B.subtilis. Biochemical and molecular characterization were done for identification of bacterial isolates. Internal transcribed regions of DNA of 16SrRNA of Isolate 1 and 2 were amplified by PCR using CAGGCCTAACACATGCAAGTC as forward primer and GGGCGGWGTGTACAAGGC as reverse primer. Blast search of amplified DNA in NCBI data revealed the identity of Isolate 1 and Isolte 2 as Bacillus thuringiensis strain a57 and stenotrophomonas maltophilia strain W2-7 respectivelly. The identity of bacteria was further confirmed by biochemical analysis. The present study was successful in identifying two bacterial antagonists (Stenotrophomonas maltophilia strain W2-7 and Bacillus thuringiensis strain a57) against root-knot nematode. Results revealed that these two isolates suppressed population of M.incognita and increased growth and yield in tomato plants. Soil drenching with these two indigenous bacterial isolates (1*10 7 cuf ml-1)@ 50 mL pot-1can be recommended to manage M.incognita in tomato without any detrimental effect on environment.